The contact and response process in business surveys: lessons from a multimode survey of employers in the UK - Peter Lynn; Emanuela Sala (University of Essex, Institute for Social and Economic Research (ISER), 2004)
On surveys of businesses, the processes of making contact and obtaining co-operation are quite different from those on more frequently studied types of surveys, such as those of households or private individuals. We describe experiences and outcomes on a business survey and discuss lessons that can be learnt in order to maximise contact and co-operation rates on future surveys. The survey in question has some valuable characteristics, including a wealth of auxiliary information. It also presents an interesting perspective on issues of privacy and confidentiality.
Keywords: 330